Harnessing the power of social media: transforming nursing education for unmatched academic success - Yasemin Erden; Handan Aydın Kahraman; Bahar Çiftçi (BMC, 2024)
Aim This study aimed to determine the effect of social media-supported learning on the academic achievement of nursing students and their social media usage levels in nursing education. Background Using social media in nursing education enables students to experience interactive learning, strengthening learning outcomes and creating an enriched learning environment with up-to-date information. Method The study was conducted as a randomized controlled study. CONSORTchecklist was completed. The subject of parenteral drug administration was explained interactively to all students by the same instructors for a total of 12 h for weeks. After the theoretical course, each skill was demonstrated by the instructor in the laboratory setting in a 24-h laboratory course with the demonstration method in line with the checklists. After the training was completed, the students filled out the necessary forms. Videos and informative images about parenteral drug applications were shared with the intervention group for 4 weeks through an Instagram page created for social media-supported learning. Questions and answers were shared on the subject every day in the story section. The answer to the question was shared in the story section the next day with explanations. At the end of the 4th training week, the students were asked to complete the necessary forms as a post-test. Changes in academic achievement and social media usage after the intervention were measured using achievement tests and the Social Media Scale in Nursing Education. Data were analyzed with SPSS 23.0. Normality was tested using the Shapiro-Wilk test. Independent t-tests and the Chi-Square test for categorical variables were used for normally distributed continuous variables. Pre-test and post-test comparisons within groups were evaluated with the Paired t-test if normality was met, or the Wilcoxon test. The effect size was calculated using Cohen's d. Results After social media-supported learning, it was found that the difference between the post-test mean scores of the nursing students in the intervention and control group was statistically significant(p < 0.001). It was also found that the average of the exam results after the training increased compared to the average before the training, and the difference between the two scores was statistically significant(p < 0.001). Conclusion Social media-supported education positively affected the academic achievements of nursing students and the level of social media use in nursing education.